KAJIAN SINTESIS GIPSUM DARI BATU GAMPING ASAL SULAWESI TENGAH - Gloria Yoanita; Mappiratu Mappiratu; Prismawiryanti Prismawiryanti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
ABSTRACT Research has been done for synthesis gypsum from limestone in Central Sulawesi. This Research aims are to know the best ratio of sulphuric acid of limestone that producer the highest CaSO4 and which areas in the Central Sulawesi as a producer of best limestone for the raw materials CaSO4. Variation ratio of sulphuric acid used is 70:25, 80:25, 90:25, 100:25, and 110:25. This Research using a group randomized design (GRD). The treatment was applied variations from limestone on the 3 areas, that is limestone from Bangkep (group 1), limestone from Buol (group 2) and limestone from Donggala (group 3). The purity of CaSO4 be analiyzed using AAS and uv-vis Spectrofotometri. The result showed that the best ratio of sulphuric acid is 110:25 and producer area of the best limestone for the raw materials of CaSO4 in the Bangkep. Keywords: Gypsum, Limestone, Sulfuric Acid, Yield, Purity